DETECTION OF MecC GENE OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS ISOLATES AT JAMBI CITY HOSPITALS - Humaryanto; Fairuz; Hanina (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: Methicillin Resistant Staphylococcus aureus (MRSA) has a low-affinity to penicillinbinding protein (PBP) in B1subclass, and is often known as PBP2a or PBP2, characterized by the presence of mecA gene. Further research found MRSA isolates that did not contain the mecA gene. They have mecA homolog gene (mecALGA251) which has similarity with the classic mecA gene, then named the mecC gene. The discovery of MRSA mecC in humans still low in prevalence.Objective: This study aimed to detect mecC gene in MRSA isolates at hospitals in Jambi.Method: This study was a descriptive study conducted in the Biomedical and Biomolecular Laboratoryof Faculty of Medicine and Health Sciences, Jambi University.Results: A total of 117 clinical specimens in the forms of purulent wound swabs of the inpatients athospitals in Jambi City has been cultured on the MSA agar. Then yellowish samples (43 isolates) were screened for susceptibity of cefoxitin (30 Âµg) by disc / diffusion test and the presence of mecA, femB and mecC genes by conventional PCR. There were 22 (51.16%) samples contained mecA, 2 (4.65%) samples had also femB gen, 1 (2.32%) samples contained femB gene only and none contained the mecC gene.Conclusion: There was no mecC gene had been found in MRSA isolates in Jambi.Keywords: PCR, MRSA, MecC, MecA, FemB